DEFICIENCY AND THE LABOR MARKET: ON THE BARRIER OF THE ESTIGMA FOR EQUAL INCLUSION AND THE LEGAL GUARANTEES FOR THE EQUALIZATION OF OPPORTUNITIES AND ACCESS - Moreira Ferreira, Oswaldo; André dos Santos Farias, Daniel; Campos de Souza Amaral, Shirlena; Gomes da Silva Muylaert Monteiro de Castro, Bianca (LINKSCIENCEPLACE, 2026)
The present work refers to a qualitative research, which seeks to articulate the concept of stigma concerning persons with disabilities, as well as the analysis of the principle of equality and the inclusion of persons with disabilities in the labor market and the legislation that Protects them. Regarding social inclusion through work, it seeks to dissociate the disability from the idea of disability, given that, currently, there is recognition of social diversity, empowering the individual for their abilities and not for their differences. Today’s society migrates to a stage where differences are no longer seen as negative points, valuing individuals by their singularities. To this end, legislation is used, which has also been modified to meet the demands of minorities, to ensure social equality based on the constitutional principles of isonomy and the dignity of the human person. As society needs to build new knowledge about the person with disabilities, they develop patterns of interaction and a set of actions favorable to their members. It is noted that the work allows the stimulus to its development and is a decisive factor in the process of social inclusion of people with disabilities, being indispensable for the construction of the individuality of the subject as active participant of the society. In order for this construction to take place, it is necessary to have multiple efforts and the participation of all segments of society, offering alternatives linked to social inclusion in order to promote a true cultural change in relation to human diversity and potentialities. In this way, it turns out that the challenges and confrontations encountered by people with disabilities are anchored in the history of humanity, revealing that the successful society is one that favors, in all areas, human coexistence and respect for diversity that It constitutes.